Never without my mobile phone: the relationship between nomophobia, social media addiction and emotion regulation difficulties - Dolapoğlu, Nazan; Türk, Ezgi; Yürür, Emre Kaan; Şahin Can, Merve; Alçı, Deniz; Tulacı, Rıza Gökçer; Baykan, Hayriye; Karlıdere, Tunay (Journal of Dependence, 2025)
Objective: Nomophobia (No MObile PHone PhoBIA) refers to the concern or fear that individuals experience when they’re without their mobile phone or they’re unfit to use it. This research aimed to elucidate the relationship between nomophobia, social media addiction, and emotion regulation difficulties in university students. Method: A total of 100 volunteer medical school students, 55 female and 45 male, with an average age of 23, are included in this study. The questionnaires included sociodemographics and social media usage characteristics, The Turkish Nomophobia Scale, the social media addiction scale, and the emotion regulation difficulties scale. The data were collected in a face-to-face manner by the researchers. Results: There was a moderately positive, statistically significant relationship between the emotion regulation difficulties scale total score, the social media addiction scale total score, and the total scores of the Turkish Nomophobia Scale. Conclusion: Emotion regulation difficulties may explain nomophobia and social media addiction. Developing emotion regulation strategies may help reduce nomophobia and addictive use of social media.